Effects of Some Antipsychotics and a Benzodiazepine Hypnotic on the Sleep-Wake Pattern in an Animal Model of Schizophrenia - Takayuki Ishida; Yoshihito Obara; Chiaki Kamei (Elsevier, 2009)
We studied the effects of antipsychotics and a hypnotic on sleep disturbance in schizophrenia using an animal model of the disease. Electrodes for the electroencephalogram (EEG) and electromyogram (EMG) were chronically implanted into the cortex and the dorsal neck muscle of rats. EEG and EMG were recorded with an electroencephalograph for 6 h (10:00 - 16:00). SleepSign ver. 2.0 was used for EEG and EMG analysis. Haloperidol and olanzapine had an antagonizing effect on the increases in sleep latency and total awake time and the decrease in total non-rapid eye movement (NREM) sleep time induced by MK-801. Olanzapine also antagonized the decrease in total rapid eye movement (REM) sleep time induced by MK-801. Aripiprazole antagonized only the increase in sleep latency induced by MK-801, whereas, risperidone, quetiapine, and flunitrazepam had no effect in the changes of sleep-wake pattern induced by MK-801. Olanzapine increased delta activity and decreased beta activity during NREM sleep. In contrast, flunitrazepam had an opposite effect. It was clarified that haloperidol and olanzapine were effective for decrease of sleep time in this animal model of schizophrenia. In addition, aripiprazole showed a sleep-inducing effect in schizophrenia model rat. On the other hand, flunitrazepam showed no beneficial effect on sleep disturbance in schizophrenia model rat. Keywords:: antipsychotic, benzodiazepine hypnotic, sleep-wake pattern, MK-801, schizophrenia